FACTORS AFFECTING THE QUALITY OF LIFE OF SUPPORT PERSONNEL IN CHULALONGKORN UNIVERSITY - Eiamlapa, Pimvisa; Maphong, Raweewan (Journal of Sports Science and Health, 2025)
Purpose This study aimed to examine the overall and domain-specific quality of life of support personnel at Chulalongkorn University, classified by gender, age, income, educational attainment, length of service at the university, and affiliated departments. Methods The sample consisted of 400 support personnel members currently employed at Chulalongkorn University in the Pathumwan district, including both male and female participants aged between 18 and 60 years, holding positions at levels P3 to P8. The research instruments included a general demographic questionnaire and the WHOQOL-BREF–THAI, a standardized instrument for assessing quality of life. Data were analyzed using descriptive statistics namely percentage, mean, and standard deviation and inferential statistics. Independent sample t-tests were conducted to compare quality of life by gender, while one-way ANOVA was used to assess differences by age, income, educational attainment, length of service, and department affiliation. Results The overall quality of life and its four domains—physical health, mental health, social relationships, and environmental factors—among support personnel were at a moderate level. When classified by gender, age, income, length of service, and department, significant differences in quality of life were found. However, no significant difference was observed with educational attainment. Conclusion The study concluded that the overall and domain-specific quality of life of support personnel at Chulalongkorn University was moderate. Variations in quality of life were significantly associated with gender, age, income, length of service, and department affiliation, whereas educational attainment was not found to be a determining factor.